Metode dan Media Pembelajaran Bahasa Arab Berbasis Internet di Era Teknologi Informasi - Muhandis Azzuhri (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Information technology era necessitate changing of learning system, mainly on method and media Arabic language learning. Arabic language learning system nowadays criticized because its monotone, traditional, and not innovative compared with other language learning. This is because absolutism and lack of creativity of Arabic learning staÂkeholders (lecturer, teacher, Kiai) to apply method and Arabic language learning media that appropriate with information technology advancement. internet- based Arabic language learning embarked because as most communicative learning media at information technology era because integrate internet and other information channel as tools to empower learning process to more creative, innovative, and competitive. .